Determining Health Perceptions and Healthy Life Style Behaviors of Vocational School of Health Services Students - Özsoy, Hatice; Şentürk, Sibel (İnönü Üniversitesi, 2021)
This study was conducted to determine health perceptions and healthy lifestyle behaviors of vocational school of health services students. The population of this descriptive study was composed of all students (890 students) who continued their education and training at Gölhisar Health Vocational High School between March-June 2019, and the sample consisted of 600 students participating in the study. The data were obtained by “Personal Information Form”, developed by the researchers, “Health Perception Scale (HPS)” and “Healthy LifeStyle Behaviors Scale (HLSBS)”. Data were analyzed using descriptive statistics, Mann-Whitney U test, Kruskal-Wallis test and Spearman correlation analysis. 88.5% of the participants were aged between 18 and 21 years, 70.8% of them were female students and 39.5% of them studied at the department of Medical Documentation and Secretariat. The students’ average total score of HPS was 50.61±6.61 and their average total score of HLSBS was 123.05±19.93. A statistically significant difference was found between the variables of the department, grades and general health status of the students and the HPS and HLSBS. A weak and positive correlation was determined between the students' HPS total score and HLSBS total score (p=0.000, r=0.196). It was found that as health perception of vocational health school students increased, so did their healthy lifestyle behaviors. It may be recommended that optional subjects be included in curriculums and courses and seminars be organized in order to maximize health perceptions and healthy lifestyle behaviors.

Bu araştırma, Sağlık hizmetleri meslek yüksekokulu öğrencilerinin sağlık algısı ile sağlıklı yaşam biçimi davranışlarının belirlenmesi amacıyla yapılmıştır. Tanımlayıcı tipteki bu çalışmanın evrenini Mart-Haziran 2019 tarih aralığında Gölhisar Sağlık Hizmetleri Meslek Yüksekokulunda eğitim ve öğretime devam eden tüm öğrenciler (890 öğrenci), örneklemi ise çalışmaya katılım sağlayan 600 öğrenci oluşturmuştur. Veriler, araştırmacılar tarafından geliştirilen “Kişisel Bilgi Formu”, “Sağlık Algısı Ölçeği (SAÖ)” ve “Sağlıklı Yaşam Biçimi Davranışları Ölçeği (SYBDÖ)” ile elde edilmiştir. Veriler; tanımlayıcı istatistikler, Mann-Whitney U testi, Kruskal-Wallis testi ve Spearman korelasyon analizi kullanılarak analiz edilmiştir. Çalışmada yer alan öğrencilerin %88.5’i 18-21 yaş aralığında, %70.8’i kadın ve %39.5’i tıbbi sekreterlik ve dokümantasyon bölümünde okumaktaydı. Öğrencilerin SAÖ toplam puan ortalaması 50.61±6.61 ve SYBDÖ toplam puan ortalaması ise 123.05±19.93 idi. Öğrencilerin okuduğu bölüm, sınıf ve genel sağlık durumu değişkenleriyle SAÖ ve SYBDÖ arasında istatistiksel olarak anlamlı fark tespit edilmiştir. Öğrencilerin SAÖ toplam puanı ile SYBDÖ toplam puanı arasında ise pozitif yönde zayıf bir ilişki belirlenmiştir (p=0.000, r=0.196). Meslek yüksekokulu öğrencilerinin sağlık algısı arttıkça sağlıklı yaşam biçimi davranışlarının da arttığı belirlenmiş olup sağlık algısı ve sağlıklı yaşam biçimi davranışlarını arttırmak için ders müfredatlarına seçmeli derslerin eklenmesi, kurs ve seminerlerin düzenlenmesi önerilebilir.
SAĞLIK HİZMETLERİ MESLEK YÜKSEKOKULU ÖĞRENCİLERİNİN SAĞLIK ALGISI VE SAĞLIKLI YAŞAM BİÇİMİ DAVRANIŞLARININ BELİRLENMESİ
Keywords: Clinical Sciences; Klinik Tıp Bilimleri